Оценка износостойкости новых модификаций алмазно-твердосплавных пластин - Свешников, И.А.; Стасюк, Л.Ф.; Заболотный, С.Д.; Смекаленко, С.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The new method of an estimation of wear resistance ATP is developed, allowing to predict their working capacity. Tests of new updatings of ATP with height diamond layer to 1,8 mm, developed in ISM are conducted. Influence of ways of processing diamond layer of plate on process of cutting of rock is studied.